Disruption of Nuclear Organization during the Initial Phase of African Swine Fever Virus Infection - Ballester, Maria (American Society for Microbiology, 2011)

(untitled)
African swine fever virus (ASFV), the causative agent of one of the most devastating swine diseases, has been considered exclusively cytoplasmic, even though some authors have shown evidence of an early stage of nuclear replication. In the present study, an increment of lamin A/C phosphorylation was observed in ASFV-infected cells as early as 4 h postinfection, followed by the disassembling of the lamina network close to the sites where the viral genome starts its replication. At later time points, this and other nuclear envelope markers were found in the cytoplasm of the infected cells. The effect of the infection on the cell nucleus was much more severe than previously expected, since a redistribution of other nuclear proteins, such as RNA polymerase II, the splicing speckle SC-35 marker, and the B-23 nucleolar marker, was observed from 4 h postinfection. All this evidence, together with the redistribution, dephosphorylation, and subsequent degradation of RNA polymerase II after ASFV infection, suggests the existence of sophisticated mechanisms to regulate the nuclear machinery during viral infection.